Road proximity, air pollution, noise, green space and neurologic disease incidence: a population-based cohort study - Weiran Yuchi; Hind Sbihi; Hugh Davies; Lillian Tamburic; Michael Brauer (BMC, 2020)
Abstract Background Emerging evidence links road proximity and air pollution with cognitive impairment. Joint effects of noise and greenness have not been evaluated. We investigated associations between road proximity and exposures to air pollution, and joint effects of noise and greenness, on non-Alzheimer's dementia, Parkinson's and Alzheimer's disease and multiple sclerosis within a population-based cohort. Methods We assembled administrative health database cohorts of 45-84 year old residents (N ~ 678,000) of Metro Vancouver, Canada. Cox proportional hazards models were built to assess associations between exposures and non-Alzheimer's dementia and Parkinson's disease. Given reduced case numbers, associations with Alzheimer's disease and multiple sclerosis were evaluated in nested case-control analyses by conditional logistic regression. Results Road proximity was associated with all outcomes (e.g. non-Alzheimer's dementia hazard ratio: 1.14, [95% confidence interval: 1.07-1.20], for living < 50 m from a major road or < 150 m from a highway). Air pollutants were associated with incidence of Parkinson's disease and non-Alzheimer's dementia (e.g. Parkinson's disease hazard ratios of 1.09 [1.02-1.16], 1.03 [0.97-1.08], 1.12 [1.05-1.20] per interquartile increase in fine particulate matter, Black Carbon, and nitrogen dioxide) but not Alzheimer's disease or multiple sclerosis. Noise was not associated with any outcomes while associations with greenness suggested protective effects for Parkinson's disease and non-Alzheimer's dementia. Conclusions Road proximity was associated with incidence of non-Alzheimer's dementia, Parkinson's disease, Alzheimer's disease and multiple sclerosis. This association may be partially mediated by air pollution, whereas noise exposure did not affect associations. There was some evidence of protective effects of greenness.